Post-transcriptional gene silencing (PTGS) in oil palms infected with coconut cadang-cadang viroid (CCCVd) variants - Wu, Ying Hooi (2012)
Post-transcriptional gene silencing (PTGS), also known as RNA silencing, is a natural host defense mechanism that regulates gene expression in eukaryotes and results in the sequence-specific degradation of single stranded RNAs (ssRNAs) from genetic elements of internal or foreign origin. Based on the detection of short interference RNA (siRNAs),several viroids have been shown to induce PTGS. Recently, Coconut cadang-caang viroid (CCCVd) variants had been detected in commercial oil palm plantations in Malaysia. CCCVd is the causal agent of the lethal Coconut cadang-cadang disease in the Philippines. Losses over 30 million coconut palms have been estimated since the disease was first reported. CCCVd variants in oil palm were reported to be present at much lower concentrations than of CCCVd in coconut palm. Reports suggested that the low concentrations of the oil palm variants could be due to PTGS. In view of this, these studies were conducted to examine the presence of PTGS targeting against CCCVd variants in oil palm, optimize the detection method and also sequence the CCCVd variants in oil palm with PTGS. Samples were collected from commercial oil palm plantations in Malaysia. Large amount of nucleic acid extractions, polyacrylamide gel electrophoresis, electroblotting, hybridization and immunological detections were optimized for detection of siRNA and the CCCVd variant. The results show that combination of Phenol-SDS extraction, 15% denaturing polyacrylamide gel electrophoresis, electrobloting and autoradiography showed the best result for the detection of CCCVd variants. siRNA were absent from the oil palm isolates that were sampled in this study, it could be due to undetectable, suppression from host or quasi species. CCCVd variants were sequenced from four symptomatic palms and one asymptomatic oil palm with Reverse-transcriptase polymerase chain reaction (RT-PCR), cloning and sequencing. The expected amplicons of about 200-300 bp were successfully amplified, cloned and sequenced. The sequence showed 99% sequence homology to CCCVd (246 nt) from coconut variants.